Revealing and Criticizing an Indonesian Edu-Tech Company’s Capitalism Ideology which Dehumanizes Indonesian Teachers: a Critical Discourse Analysis - Cahya Pratama Windianto (Universitas Negeri Yogyakarta, 2022)
This paper aims to reveal the hidden capitalism ideology of a certain edu-tech company from the memorandum the company released which talks about the newest penalty system for the teachers. Not only limited to reveal, but this paper also criticizes why the ideology can be dehumanizing for the teachers. To reveal and criticize the ideology, the approach of critical discourse analysis as the methodology is conducted. This paper carefully reads, describes, interprets, and analyzes the text by connecting the assumption and interpretation with scientific theories such as marxism and humanistic education. Based on the findings, it is concluded that the capitalism ideology found from the text delivered by the company dehumanizes the teachers since the company still sanctions the teachers with a penalty although they suffer from unavoidable accidents.Keywords: Capitalism, critical discourse analysis, humanistic education, Marxism